Pengaruh Keaktifan Berorganisasi Terhadap Kemampuan Mengelola Waktu Siswa SMA Negeri - Hana, Serli; Sunarni, Sunarni; Juharyanto, Juharyanto (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: The aims of this research are: (1) to describe the level of activeness in student organizations at SMAN in Kebumen Regency; (2) describe the ability to manage time for SMAN students in Kebumen Regency; (3) knowing the effect of being active in an organization on the ability to manage the time of high school students in Kebumen Regency. This research is a correlational descriptive research. The sampling technique using proportional stratified random sampling was used in each school with a total sample of 379 students. The analysis technique used is descriptive analysis, correlational, and hypothesis testing with the help of IBM SPSS statistics 25. The results of this study are: (1) the level of activeness in the organization of high school students in Kebumen Regency belongs to the high category; (2) the ability to manage time for high school students throughout Kebumen Regency is in the high category; (3) there is a significant and positive influence between organizational activity on the ability to manage time for high school students in Kebumen Regency.Keywords: organizational activity; time management; skills Abstrak: Tujuan penelitian ini yakni: (1) mendeskripsikan tingkat keaktifan berorganisasi siswa SMAN se-Kabupaten Kebumen; (2) mendeskripsikan kemampuan mengelola waktu siswa SMAN se-Kabupaten Kebumen; (3) mengetahui pengaruh keaktifan berorganisasi terhadap kemampuan mengelola waktu siswa SMAN se-Kabupaten Kebumen. Penelitian ini merupakan penelitian deskriptif korelasional. Teknik pengambilan sampel menggunakan Proporsionate Stratified Random Sampling digunakan di masing-masing sekolah dengan jumlah sampel total sebanyak 379 siswa. Teknik analisis yang digunakan yakni teknik analisis deskriptif, regresi, dan uji hipotesis dengan bantuan IBM SPSS Statistic 25. Hasil penelitian ini yakni: (1) tingkat keaktifan berorganisasi siswa SMAN se-Kabupaten Kebumen tergolong dalam kategori tinggi; (2) kemampuan mengelola waktu siwa SMAN se-Kabupaten Kebumen tergolong dalam kategori tinggi; (3) terdapat pengaruh yang signifikan positif antara keaktifan berorganisasi terhadap kemampuan mengelola waktu siswa SMAN se-Kabupaten Kebumen.Kata kunci: keaktifan berorganisasi; kemampuan mengelola waktu; skills